"The adult gaze": exploring the representation of children in television news in Albania. Issue 4 (1st October 2016) - Kaziaj, Emiljano
Abstract: This article investigates the portrayal of children in Albanian television news and introduces the term "adult gaze" to describe the construction of news items in such a way as to reinforce the perspectives of adults on children. Journalists choose to construct news items related to children by focusing the story around an adult figure, most often a politician, and giving his/her views on the issue being discussed, which points to unequal power relations between children and adults. A monitoring process over a period of three months was carried out for three national television channels. From a total of 4416 news items, 154 items were identified and were subject to further quantitative and qualitative content analyses. Based on our findings, news media portray children in limited roles as objects of emotional appeal, victims or performers. How news media think of and represent children can play a crucial role in shaping our perceptions of them and their positioning in society.